Consequence of Use of Alcoholic Beverages in Modern Life-Style and Remedy with Yoga and Ayurveda - Biswal, Surendra Kumar; Patnaik, Supriti (International Research Journal of Ayurveda & Yoga, 2023)
economic problem may occur. Sometimes the family members as well as friends also ignore to such activities of user knowingly or unknowingly. Users often take beetle with tobacco products in order to conceal the fact, which may also harm to their body. As the time passes and if it is not controlled by him-self or family, then such person falls down to another world, from where he does not want to come back and he makes distances from family as well as good friends. At last a stage comes where he becomes ruined socially, economically, physically and mentally. Some users even try to commit suicide due to frustration. Homicidal activities and sexual violence may also be noticed. Now-a days alcoholism is a commonest cause for incidents of murder and rape as well as traffic accidents. Hence if the consumer adopt the lifestyle described in Ayurveda and Yoga, then one can give up the addiction of alcohol and able to lead a happy and healthy life.